2008
DOI: 10.1093/hmg/ddn193
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of β-catenin in XY gonads causes male-to-female sex-reversal

Abstract: During mammalian sex determination, expression of the Y-linked gene Sry shifts the bipotential gonad toward a testicular fate by upregulating a feed-forward loop between FGF9 and SOX9 to establish SOX9 expression in somatic cells. We previously proposed that these signals are mutually antagonistic with counteracting signals in XX gonads and that a shift in the balance of these factors leads to either male or female development. Evidence in mice and humans suggests that the male pathway is opposed by the expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
269
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 309 publications
(280 citation statements)
references
References 28 publications
4
269
0
Order By: Relevance
“…An alternative model might consider that the amplifications abrogate SOX9 silencing by moving a hypothetical negative regulatory Testis development in the absence of SRY A Vetro et al element located upstream of RevSex (negative gonadal regulatory element (NGRE), dashed blue line in Figure 3), too far away to exert any influence on SOX9 promoter. In fact, SOX9 repression needs to be maintained on the XX background both in the developing gonad 26 and in the ovary, 27 in order to ensure the differentiation and maintenance of ovarian cell fate. NGRE would not be displaced, but rather included in duplications associated with brachydactylyanonychia but not with sex reversal (dark green in Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative model might consider that the amplifications abrogate SOX9 silencing by moving a hypothetical negative regulatory Testis development in the absence of SRY A Vetro et al element located upstream of RevSex (negative gonadal regulatory element (NGRE), dashed blue line in Figure 3), too far away to exert any influence on SOX9 promoter. In fact, SOX9 repression needs to be maintained on the XX background both in the developing gonad 26 and in the ovary, 27 in order to ensure the differentiation and maintenance of ovarian cell fate. NGRE would not be displaced, but rather included in duplications associated with brachydactylyanonychia but not with sex reversal (dark green in Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…The cellular context is essential for the choice of the pathway to be activated as exemplified by WNT4. While WNT4 is able to activate canonical WNT signaling in gonadal development (Maatouk et al 2008, Liu et al 2010), it appears to induce CTNNB1-independent pathways in the kidney (Burn et al 2011). In addition to its role in canonical WNT signaling, CTNNB1 is also an important component of adherent junctions, which regulates patterning and morphogenesis.…”
Section: Wnt4 a Wingless Family Gene Involved In Many Biological Promentioning
confidence: 99%
“…In 2006, Prof. Giovanna Camerino et al identified R-spondin1 (RSPO1), a WNT signaling pathway activator, as a novel key factor involved in sexual and ovarian differentiation (Parma et al 2006). After 2 years, Prof. Blanche Capel et al showed that genetic induction of WNT/b-catenin signaling can modify the fate of the gonad by promoting the ovarian development from a gonad programed to become a testis (Maatouk et al 2008). This complemented their previous work on Wnt4, another player in the WNT signaling pathway, which showed that sex determination is governed by a balance between two antagonistic pathways (Kim et al 2006) and firmly established WNT/b-catenin signaling as a key pathway involved in female differentiation.…”
mentioning
confidence: 99%
“…[23] WNT4 and RSPO1 both induce stabilization of beta-catenin, and it is known that ectopic expression of a stable form of betacatenin in XY gonads can lead to male-to-female sex reversal. [24] The antagonism between FGF and Wnt signals during chondrocyte differentiation is well known. Indeed, Fgf promotes Sox9 expression and Wnt signaling leads to its degradation ( [25] and references therein).…”
Section: Foxl2: a Molecular Actor In The Spotlightmentioning
confidence: 99%